Top 100 cited research on COVID-19 vaccines: A bibliometric analysis and evidence mapping - Liping Yu; Caihua Xu; Mingyue Zhang; Yongjia Zhou; Zhiruo Hu; Lin Li; Yiyi Li; Jinhui Tian; Mingli Xu (Human Vaccines & Immunotherapeutics)
The outbreak of the COVID-19 has seriously affected the whole society, and vaccines were the most effective means to contain the epidemic. This paper aims to determine the top 100 articles cited most frequently in COVID-19 vaccines and to analyze the research status and hot spots in this field through bibliometrics, to provide a reference for future research. We conducted a comprehensive search of the Web of Science Core Collection database on November 29, 2023, and identified the top 100 articles by ranking them from highest to lowest citation frequency. In addition, we analyzed the year of publication, citation, author, country, institution, journal, and keywords with Microsoft Excel 2019 and VOSviewer 1.6.18. Research focused on vaccine immunogenicity and safety, vaccine hesitancy, and vaccination intention.